Tulips in Bloom An Anthology of Modern Central Asian Literature - McGuire, Gabriel; Fort, Chris; Caffee, Naomi; Laskin, Emily; Hodgkin, Samuel; İğmen, Ali F. (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
XXII, 511 p. 1 illus.